Rhetorical structure of technical research articles - Musa, Nurul Farahin (2017)
Research articles have been regarded as one of the most common medium to communicate new findings to the academic community. Genre analysis is one of the most common ways to analyse the rhetorical structure of a text and has been proven to be useful in providing an insight on how the structure a text is constructed including research articles. Previously, there are many genre analysis and rhetorical organisation studies on research articles from different disciplines. Some of the studies focused on the whole structure and some of them focused on discrete section of research articles. This study attempts to identify the macrostructure of technical research articles and the most frequent move for each section in technical research articles. The present study adopts a corpus-based analysis. The corpus for this study comprises 60 journal articles from an engineering discipline, retrieved from the Scopus websites. The findings revealed that there are similarities and differences in terms of the application of moves between the proposed framework and the present corpus. The most frequent move for each section is also identified. Some of the moves in the framework from the previous studies are not applicable in the present corpus and some are. Findings from this study suggest that there are crucial moves in each section of research articles which need to be understood and adopted by writers in writing a research article and understanding the macrostructure of research articles can help the writers to prepare their research articles in a proper way and be accepted in international journals.